HOME-SCHOOL LINK A KEY FACTOR TO EXPLAIN AN IMPRESSIVE PERFORMANCE OF CHINESE-AUSTRALIAN HIGH SCHOOL STUDENTS - Malik, Ranbir Singh (International Journal of Education, 2011)
This study focused on congruency of culture of home and school of children from Chinese-Australian families as a major factor in their academic success. Qualitative approach wasused for uncovering three key things, namely, 1) conditions and interactions at home; 2)children’s behavior and interaction in classroom; 3) children’ activities after school hoursand at weekends. The approach considered to be appropriate to capture what teachers,parents and children say and do as a product of how they interpret the complexity of theirworld. Data collected by using ethnographic techniques, mainly participant observationand conversational interviews. There were seven children from five Chinese-Australianfamilies residing in Perth metropolitan area involved in the study. The families immigratedfrom Malaysia, Singapore, and Hong Kong. Analysis indicated that Chinese-Australianparents pushed their children far beyond their limits in their drive for academic excellence.They made their home suitable for studying and ensured continuity between homes andschool. Impulse control, deferment of short term gratification, effort/hard work, andscholastic achievement were Chinese cultural values implanted by the parents. Chinese-Australian children met most of their teachers’ demands. Consequently, their interactionswith their teachers were in more positive ways.Key words: Chinese-Australian families, impressive performance students